2019
DOI: 10.1002/jcla.22896
|View full text |Cite
|
Sign up to set email alerts
|

ABCA1 variants rs2230806 (R219K), rs4149313 (M8831I), and rs9282541 (R230C) are associated with susceptibility to coronary heart disease

Abstract: BackgroundTo investigate the association between three single nucleotide polymorphisms (SNPs) of ABCA1 gene and susceptibility to coronary heart disease (CHD) in Chinese Han population.MethodsA total of 484 CHD patients and 488 controls were included in the study. Three SNPs rs2230806 (R219K), rs4149313 (M8831I), and rs9282541 (R230C) in ABCA1 gene were genotyped by SNaPshot.ResultsSingle nucleotide polymorphism rs1800977 was associated with susceptibility to CHD (AA vs GG, P = 0.013; A vs G, P = 0.029; recess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…Some studies have shown that ABCA1 rs4149313 is associated with coronary heart disease, 21,22 while we identified a significant association between rs4149313 and T2DM in three genetic models in this study. Conversely, while ABCB1 rs1128503 has previously been associated with hepatocellular carcinoma and breast cancer, 23,24 we found no association between rs1128503 and T2DM in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Some studies have shown that ABCA1 rs4149313 is associated with coronary heart disease, 21,22 while we identified a significant association between rs4149313 and T2DM in three genetic models in this study. Conversely, while ABCB1 rs1128503 has previously been associated with hepatocellular carcinoma and breast cancer, 23,24 we found no association between rs1128503 and T2DM in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Genetic factors are key to an individual’s susceptibility to CHD, accounting for 30–60% of interindividual variation in the risk of CHD [7]. Some studies have shown genetic polymorphisms are associated with CHD risk in the Chinese populations, such as ABCA1 and paraoxonase 1 genes [8]. Among other risk factors are advanced age, diabetes, hypertension, increased total and low-density lipoprotein cholesterol in plasma, increased plasma triglycerides (TGs), and decreased plasma high-density lipoprotein (HDL) cholesterol [9].…”
Section: Introductionmentioning
confidence: 99%
“…The association between altered HDL concentrations and many other ABCA1 variants, including R219K (rs2230806) is well established by previous studies [ 76 , 77 , 78 ], which are linked to the development of ischemic heart disease (IHD) by the increasing risk of atherosclerosis in the general population [ 79 ]. According to recent studies, it has been revealed that the effects on plasma HDL cholesterol level and the incidence and severity of coronary heart diseases depend mostly on the distribution and frequency of SNPs in different regions of the ABCA1 gene as well as different populations [ 80 , 81 ]. Since similar SNPs show similar or opposite effects, widespread mutagenesis studies are required to investigate the exact role and the loss of function of ABCA1 upon G1050V and S1067C mutations.…”
Section: Discussionmentioning
confidence: 99%